Recent Advances in Biological Nanodevices and Biosensors: Insights into Applications and Technological Innovations - Shivakumar, Neeta (Malaysian NANO-An International Journal, 2024)
This paper explores recent advances in the detection of viruses and metals, focusing on how biosensors are revolutionizing environmental management and healthcare. Biosensors have transformed fields such as medical diagnostics by enabling the detection of biological targets at low concentrations. Specifically, graphene field-effect transistor (FET)-based immunosensors have emerged as powerful tools for swiftly and accurately identifying biological targets, opening new avenues in these areas. Furthermore, improvements in metal detection have enabled the monitoring of electrical activity in non-excitable cells, advancing research into cancer bioelectricity and its therapeutic applications. These advancements demonstrate how nanotechnology can innovate approaches in healthcare, offering more sensitive, adaptable, and efficient methods. Additionally, progress in cellular electrophysiology holds promise for enhancing treatments in neurology, cardiology, and regenerative medicine. These advancements can lead to better patient outcomes and expedite the development of bioengineered tissues and organs with integrated electrical properties. This paper explores these groundbreaking applications of biosensors in environmental and medical sciences, highlighting their transformative potential and future directions.